Synthesis of flexible polyurethane foams by the partial substitution of polyol by steatite - Plínio César de Carvalho Pinto (Polímeros: Ciência e Tecnologia, 2018)
This work describes the synthesis of composites steatite/flexible polyurethane by replacing 4.5 wt. % of polyol with steatite rock powder. We evaluated two mechanical properties of composites (comfort factor and support factor) for various formulations based on a fractional factorial design. The new synthesized composites showed higher support factor, greater comfort factor, and lower cost, compared to conventional flexible polyurethane foams. There is not a significant change in the chemical composition of the foams, due to substitution of 4.5 wt. % polyol by steatite. However, there was a decrease in cell size and greater interaction between the hard segments of the composite.